Hip-hop from dancers’ viewpoint: Dance, lifestyle, and/or subculture? - Snežana Damjanović; Boris Popović; Ivana M. Milovanović; Tijana Šćepanović (Exercise and Quality of Life)
The paper presents the results of field research on the population of dancers – members of the hip-hop community who are “contestants” in battles. The field research was carried out in April 2022 on a sample of dancers aged 17 to 40 (N = 31). The research results indicate that the hip-hop community in Serbia is small, but that such battles in specific forms contribute to the community’s maintenance and expansion. Battles also play a significant role in the progression and expression of dancers as individuals. Dancers consider hip-hop to be not only an art form but much more, hip-hop is synonymous with a lifestyle and a “way of looking at the world” for dancers. Although the research was carried out on a small sample, it represents the author’s pioneering contribution to a deeper understanding of the hip-hop community in Serbian society. It also indicates the need to carry out compatible research in the future.